Limited possibilities: agency and subaltern subjectivity in four South African allegories - Fick, Angelo Carlo (Department of English Language and Literature, 2020)
This thesis examines the representation of the negotiation of black women's subjectivity in four South African allegorical novels. Using aspects of postmodern discourse, and feminist and postcolonial literary and cultural theories on identity formation and subjectivity, I propose that it is in the allegorical mode that the four writers are able to offer black women as female gendered subalterns the space to negotiate subjectivity and to assert agency. Given the history of sexism, racism and imperialism in South Africa, the politics of place impact crucially on the practice of writing literature, so that the tensions between the representation of others and self-representation becomes crucial in identity formation. Through the four texts, I propose that there is a spectrum of practices, and that each offers different possibilities for black women's subject formation: from the most limiting liberal discourses, through the interrogation of those discourses, to an autobiographical moment of self-reclamation.